Future Treatment of Neuropathic Pain in Spinal Cord Injury: The Challenges of Nanomedicine, Supplements or Opportunities? - Giuseppe Forte; Valentina Giuffrida; Angelica Scuderi; Mariella Pazzaglia (Biomedicines, 2022)
Neuropathic pain (NP) is a common chronic condition that severely affects patients with spinal cord injuries (SCI). It impairs the overall quality of life and is considered difficult to treat. Currently, clinical management of NP is often limited to drug therapy, primarily with opioid analgesics that have limited therapeutic efficacy. The persistence and intractability of NP following SCI and the potential health risks associated with opioids necessitate improved treatment approaches. Nanomedicine has gained increasing attention in recent years for its potential to improve therapeutic efficacy while minimizing toxicity by providing sensitive and targeted treatments that overcome the limitations of conventional pain medications. The current perspective begins with a brief discussion of the pathophysiological mechanisms underlying NP and the current pain treatment for SCI. We discuss the most frequently used nanomaterials in pain diagnosis and treatment as well as recent and ongoing efforts to effectively treat pain by proactively mediating pain signals following SCI. Although nanomedicine is a rapidly growing field, its application to NP in SCI is still limited. Therefore, additional work is required to improve the current treatment of NP following SCI.